Geschäftsmänner zwischen Makedonien und Moesia Superior - Sverkos, Elias (Studia Europaea Gnesnensia, 2017)
In this paper on the basis of the funerary inscription of a conductor named Gamicus, which was found in Hagio Pnevma (territorium of the Roman colony of Philippi), are examined the relations between Macedonia, Moesia Inferior and probably Epirus. Gamicus seems to belong to the senatorial family of Pontii; they are attested in the inscriptions from Ulpianum and its region and were even related by marriage with another senatorial family, i.e. the Furii. Both families owed their social position to the mines. Apart from the well known senator Gaius Furius Octavianus and his mother Furia Caecilia, the activity of the domus Furiana is known by the presence of its vilici and servi. Epigraphical testimonies show that the large estates of the Furii as well as the Pontii were situated in the southern part of Ulpianum and in the northwestern part of Scupi. Although the gentilicium Furius is also widespread in the province of Macedonia, of particular interest to our subject, however, seem to be two inscriptions from the territorium of the Roman colony of Philippi. The first one is the epitaph erected by M. Varinius M. l. Celer for himself, his wife Varinia Marita, his daughters Primigenia and Pyralis as well as his son-in-law Furius Alcimus. Τhe second inscription (probably a dedication) lists the military offices of D. Furius Octavius Secundus, originally from Cures Sabinis, as well as the privileges bestowed to him by two colonies, Actia Nicopolis et Ulpia... The identification of Furius Alcimus with an homonymous libertus maternus of Furius Octavianus, referred in a passage of Ulpian, should be excluded. On the other hand, the presence of D. Furius Octavius Secundus in Philippi may nevertheless be connected to the exploitation of mines and quarries of this region. Furthermore, it is possible that he is an ancestor of C. Furius Octavianus and has prepared the requirements for the wealth of the domus Furiana and its adlectio in senatum.